Molecular characterization of allergens in raw and processed kiwifruit. Issue 2 (March 2015) - Uberti, Francesca; Peñas, Elena; Manzoni, Yuri; di Lorenzo, Chiara; Ballabio, Cinzia; Fiocchi, Alessandro; Terracciano, Luigi; Restani, Patrizia
Abstract: Background: The prevalence of allergy to kiwifruit is increasing in Europe since the last two decades. Different proteins have been identified as kiwifruit allergens; even though with geographic differences, Act d 1, a cysteine protease protein of 30 kDa, and Act d 2, a thaumatin‐like protein of 24 kDa, are normally considered the most important. The aim of this study was (i) to identify at molecular level the sensitization pattern in a group of well‐characterized patients allergic to kiwifruit and (ii) to assess the role of technological treatments on kiwifruit allergenic potential. Methods: The differences in the pattern of antigenicity between fresh and processed kiwifruit were evaluated by both immunoelectrophoretic techniques and clinical tests. Results: In the group of patients included in this study, three proteins were identified as major allergens in fresh kiwifruit, as the specific sensitization was present in ≥50% of the subjects. These proteins corresponded to actinidin (Act d 1), pectin methyl aldolase (Act d 6), and thaumatin‐like protein (Act d 2). Kiwellin (Act d 5) and proteins of Bet v 1 family (Act d 8/act d 11) were also recognized as minor allergens. Immunoreactivity was totally eliminated by industrial treatments used for the production of kiwifruit strained derivative. Conclusions: In this group of allergic children, the technological treatments used in the production of kiwifruit strained product reduced drastically the allergenic potential of kiwifruit.